Alokacja kosztów na inwestycje w linie biznesowe jako narzędzie wspomagające podejmowanie decyzji w przedsiębiorstwie - Oppenauer, Bartosz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The article presents the legal and business recommendations concerning the allocation of costs to the business lines in the environment of a company providing financial services to the market. It presents the advantages of this method, which provides valuable business information to the board members. The process of achieving so called full “ABC” method is very complicated, and requires longer time. The “ABC” method complies approximately 80% of all processes (products) in the company. Until then, we can use a simplified method presented in the article, and basing on that, we can make conclusions and decisions aiming at the smooth development of the company. The presented model may be a good basis for further evolution and development of the concept of investments in the business lines.